A shallow water population of Pronotogrammus martinicensis (Guichenot, 1868) (Teleostei: Serranidae: Anthiinae) from South-western Atlantic, Brazil - Carvalho-Filho, Alfredo; Ferreira, Carlos E. L.; Craig, Matthew (Zootaxa, 2009)
A population of Pronotogrammus martinicensis (Guichenot, 1868) is described and recognized as a unique shallowwater variation of the species from the Brazilian South-Eastern coast, based on genetic, morphologic and ecological data. It is distinguished from the deep water population by its smaller eye, longer snout, shorter pectoral-fin, color of the adults, and habitat depth.